The Impact of the use of Video Through the Android Application as an Anemic Educational Media on Increasing Knowledge about Anemia On Adolescent Girls - Meria Turnip; Yessy Arisman (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2022)
Anemia in adolescents is one of the nutritional problems in the world. One of the efforts to prevent anemia early is to provide anemia education to improve knowledge and attitude of young women about anemia. The purpose of this study was to analyze the influence of using video through the android application as an education media for anemia on increasing knowledge and attitudes about anemia in adolescent girls. This method of research type was quasi experiment with control group desigh pre test?post test. The research population and sample in this study were 80 and XI female teenagers in SMA 6 Yogyakarta as many as 80 people selected using proportional stratified random sampling technique. The data collection instruments used questionnaire.The data analysis used paired samples t-test and independent samples t-test. There are differences in the increase in knowledge and attitudes that are meaningful before and after anemia education is given using video through the android application and using lectures. The difference in the increase in knowledge in the video usage group through the android application is 26.88 and in the lecture group by 16.38. Difference in the increase in attitudes in the group of video use through android applications amounted to 21.96 and in the lecture group amounted to 19.06 with p = 0.001 (<0.05). There is an influence of the use of video through an android application to increase knowledge and attitudes about anemia in adolescent girls.